Vampire : the complete guide to the world of the undead - Dunn-Mascetti, Manuela (New York, NY : Viking Studio Books, 1992)
Just in time for Halloween--a spine-tingling yet tongue-in-cheek look at the world's most popular ghoul. Drawing from dark myths and legends gathered over thousands of years, Vampire is a fascinating compendium of cautionary tales and hearsay, of written chronicles and first-hand encounters withck angels that stalk the night.
Introduction: The Doors to Darkness -- Ch. 1. The Anatomy of a Vampire. Grave Discoveries. Beyond the Physical -- Ch. 2. Birth of the Undead. The Revenant. Trespassing the Gates of Death. Supernature. Mirror Images. Hidden Practices. Disposed to be a Vampire. Destined to be a Vampire. Made to be a Vampire. Vampire's Undoing -- Ch. 3. The Ways of the Vampire. Progress towards Immortality. Intrinsic Perils. A Vampire's Convenience. Bloodlust of the Countess Bathory. Dressing for Dinner -- Ch. 4. In Search of Count Dracula. A Journey into Dracula Country. Home of the Blood Drinker. Prince Dracula the Impaler. The Dracula Clan. Dracula's Death, Dracula's Birth -- Ch. 5. Family of Vampires. Lord Ruthven. Varney the Vampire. The Knight Azzo. Carmilla. Julia Stone. The Girl with the Hungry Eyes. Count Dracula: Prince of Darkness -- Ch. 6. The Vampire Library. The Horror House of Lords. The Literary Dracula. Polidori's Vampyre -- Ch. 7. Awesome Beginnings. Corridors of Glower. Death Lies Bleeding. Naming the Dead. Ascending the Vampire Line. Far-Far East -- Ch. 8. How to Kill a Vampire. Preventing the Dead. Preventing the Vampire. Killing the Vampire.
Originally published: Chronicles of the vampire. Great Britain : Bloomsbury, 1991.
Keywords: Vampires